Liberalisation of Trade in Renewable-Energy Products and Associated Goods Charcoal, Solar Photovoltaic Systems, and Wind Pumps and Turbines - Steenblik, Ronald (OECD Trade and Environment Working Papers, 2005)
Numerous studies and events over the past several years have stressed the importance of eliminating barriers to trade in renewable forms of energy and the technologies used to exploit them, as part of a broader strategy to reduce dependence on more-polluting and less secure energy sources. This paper examines the implications of liberalising trade in renewable energy, focussing on several representative fuels and technologies (charcoal, solar photovoltaic systems and their complements, and wind turbines and wind pumps). Eliminating tariffs on renewable energy and associated goods - which are 15% or higher on an ad valorem basis in many developing countries - would reduce a burden on consumers of energy, particularly people living in rural areas of developing countries, as it is in such areas that many renewableenergy technologies are making, and are likely to make, their greatest contribution. Manufacturers located in OECD countries would benefit from increased trade in renewable-energy technologies and components, but so would a growing number of companies based in developing countries. The elimination of tariffs would also help to level the playing field between aid-financed goods, which often benefit from tariff waivers, and goods imported through normal market transactions, which often do not. For the maximum benefits of trade liberalisation in renewable-energy technologies to be realised, however, additional reforms may be required in importing countries' domestic policies, especially those affecting the electricity sector in general, rural electrification in particular, and the environment